Volume 1: Offshore Technology; Special Symposium on Ocean Measurements and Their Influence on Design 2007
DOI: 10.1115/omae2007-29756
|View full text |Cite
|
Sign up to set email alerts
|

Time Domain Simulations of Side-by-Side Moored Vessels: Lessons Learnt From a Benchmark Test

Abstract: Time domain simulations are used extensively to assess the availability of turret moored terminals for offloading operations. The availability analysis provides a key input when assessing the economical viability of a project. In this context, it was deemed important to perform a benchmark study. Three programs have been used: AQWA-DRIFT - an ANSYS product maintained by Century Dynamics and used at SBM, LIFSIM and aNySIM both developed in MARIN. Five environments including wind, waves and current have been sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 4 publications
1
14
0
1
Order By: Relevance
“…The analysis of multi-body hydrodynamic interactions have also being studied in time domain [21,2,22,23]. This approach is often used when the fully-coupled analysis involving not only the bodies, but also the mooring lines and fenders must be assessed, a situation in which a time domain approach must be necessarily applied.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of multi-body hydrodynamic interactions have also being studied in time domain [21,2,22,23]. This approach is often used when the fully-coupled analysis involving not only the bodies, but also the mooring lines and fenders must be assessed, a situation in which a time domain approach must be necessarily applied.…”
Section: Introductionmentioning
confidence: 99%
“…As an exercise, if one considers a 1:150 scale factor, then the length of the geosim in full-scale would be 300 m, which may be considered a reasonable value for LNG ship vessels and the S 1 gap (0.05 m) would be come 7.5m, similar to the ones reported in literature for full scale operations (Naciri et al, 2007)). In addition, as will be further presented in this thesis, the computational results indicated that, for the multibody configurations here studied, the gap resonant frequencies are expected to occur around 9.0 s (in a 1:150 full scale) which may be considered as a typical operational peak period for sea waves.…”
Section: Configurations Studiedmentioning
confidence: 55%
“…Stiffness and pretension values of the moorings, that can be used as initial reference values, were reported in Naciri et al (2007) considering mooring lines loaded at 15 tons in the neutral position in calm water. The safe working load (SWL) of the 44 mm steel wires was assumed in their analysis to be 681 kN (55 % of MBL).…”
Section: 2)mentioning
confidence: 99%
See 2 more Smart Citations